Beyond Factory Walls - Rubiansyah, Faris (PCD Journal, 2024)
This study explores the practice of Community Unionism (CU) as a response to the challenges that member of labor union faced in the area of Mega Regency Housing complex in Bekasi Regency, Indonesia. CU emerges as an alternative strategy that expands the role of union member from mere workers in the workplace to be part of the wider community. CU views workers are not only as economic entities, but also social ones, which in return can strengthen social solidarity among union member and political bargaining power. This research uses qualitative methods, including literature review, in-depth interviews, observation, and document analysis, to answer a question and analyze how CUs operate in one of housing complexes populated by union members in the region. The results show that CUs are able to improve the bargaining position of workers while providing significant benefits to local communities. This study contributes to the Indonesian labor literature by filling the knowledge gap regarding CUs in Indonesia, as well as offering insight into the potential of CUs in strengthening the labor movement and promoting social justice at the community level. The research emphasizes the importance of community-based approaches in contemporary labor movement strategies to achieve broader social transformation.